PEMBERDAYAAN UKM BATIK MELALUI PENGEMBANGAN DESAIN MOTIF BERBASIS KEARIFAN LOKAL: UPAYA MEMBANGUN BRAND IMAGE BATIK JOMBANG [EMPOWERMENT OF BATIK SMEs THROUGH DEVELOPMENT OF LOCAL WISDOM BASED MOTIF DESIGN: EFFORTS TO BUILD BRAND IMAGE OF BATIK JOMBANG] - Nugroho Mardi Wibowo; Karsam Karsam; Yuyun Widiastuti; Siswadi Siswadi (Jurnal Sinergitas PKM & CSR, 2019)
At present, every region in Indonesia is competing to develop batik in accordance with the local characteristics of their respective regions. One area that has recently developed batik is Jombang Regency. Based on the Roadmap for Strengthening Regional Innovation Systems, Batik Jombang is set as one of the regional superior products. But until now, the batik motifs developed have not described Jombang's local wisdom. We conduct community service of the Regional Superior Product Development Program (PPPUD) in Jatipelem Village, Diwek District, Jombang Regency. The purpose of this program is to improve the quality of products through the development of batik designs based on Jombang’s local wisdom. Second, expanding market segments, not only in Jombang but also in other regions including outside of East Java Province. The method is training in developing batik motifs based on Jombang’s local wisdom, mentoring, monitoring and evaluation. Secondly, assistance is related to promotion strategies and involving SMEs in a national-level exhibition. This program has produced two new batik motifs based on local wisdom, namely “Jombang Beragam” and “Kopi Excelsa”. Second, SMEs already understand and are able to implement promotional strategies in running their business. Third, there is the addition of two new market segments.